Medicinal herbs and multiple sclerosis: Overview on the hard balance between new therapeutic strategy and occupational health risk - Costantini, Erica; Masciarelli, Eva; Casorri, Laura; Di Luigi, Marco; Reale, Marcella (Frontiers in Cellular Neuroscience, 2022)
Multiple sclerosis (MS) is an autoimmune disease characterized by demyelination and axonal loss of the central nervous system (CNS). Despite its spread throughout the world, the mechanisms that determine its onset are still to be defined. Immunological, genetic, viral, and environmental factors and exposure to chemicals may trigger MS. Many studies have highlighted the anti-inflammatory and anti-oxidant effects of medicinal herbs, which make them a natural and complementary treatment for neurodegenerative diseases. A severe reduction of several MS symptoms occurs with herbal therapy. Thus, the request for medicinal plants with potential beneficial effects, for MS patients, is constantly increasing. Consequently, a production increase needs. Unfortunately, many medicinal herbs were untested and their action mechanism, possible adverse effects, contraindications, or interactions with other drugs, are poorly or not investigated. Keeping in mind the pathological mechanisms of MS and the oxidative damages and mitochondrial dysfunctions induced by pesticides, it is important to understand if pesticides used to increase agricultural productivity and their residues in medicinal plants, may increase the risk of developing MS in both workers and consumers. Studies providing some indication about the relationship between environmental exposure to pesticides and MS disease incidence are few, fragmentary, and discordant. The aim of this article is to provide a glance at the therapeutic potential of medicinal plants and at the risk for MS onset of pesticides used by medicinal plant growers and present in medicinal herbs.